Analysis of the Effect of Basic Infrastructure and Human Resources on Gross Regional Domestic Product in Indonesia in 2017-2021 - Fitrahmayudi, M. Razaka; Ambya, Ambya (International Journal of Social Science, Education, Communication and Economics, 2024)
Indonesia, an archipelago with a diverse and growing population of 278.69 million as of mid-2023, faces both advantages and challenges in its pursuit of becoming a developed country. The key challenge lies in the unequal distribution of infrastructure development, especially in remote areas. Economic growth, driven by increased goods and services, is closely tied to infrastructure such as roads, electricity, and water distribution. This study analyzes the impact of these infrastructural elements and labor force participation on economic growth, measured by Gross Regional Domestic Product (GRDP), across 34 provinces from 2017 to 2021. Using panel data regression, the results reveal that road length, electricity distribution, and clean water distribution have significant positive effects on GRDP. However, labor force participation shows an insignificant impact. Together, these variables explain 57% of GRDP growth. The findings highlight the critical role of infrastructure in economic development, with provinces like Jakarta leading the growth while regions like North Maluku lag behind. Improving infrastructure and addressing regional disparities are essential to enhancing Indonesia’s overall economic performance.